Al2O3 Thin Films on Magnesium: Assessing the Impact of an Artificial Solid Electrolyte Interphase - Sahadeo, Emily; Rubloff, Gary; Lee, Sang Bok; Lin, Chuan-Fu (Frontiers in Energy Research, 2021)
Among the many emerging technologies under investigation as alternatives to the successful Lithium-ion battery, the magnesium battery is promising due to the wide availability of magnesium, its high volumetric capacity, and the possibility for safety improvements. One of the largest challenges facing rechargeable magnesium batteries is the formation of a passivation layer at the Mg metal anode interface when reactive species in the electrolyte are reduced at the electrode-electrolyte interface. To control the solid electrolyte interphase in Lithium batteries, protective layers called artificial solid electrolyte interphase (ASEI) layers have been successful in improving Li metal anode performance. The approach of protecting Mg metal anodes from electrolyte degradation has been demonstrated by fewer studies in the literature than Li systems. In this work, we discuss the properties of Al2O3 thin films deposited using atomic layer deposition as an artificial solid electrolyte interphase at the Mg anode. Our results demonstrate that Al2O3 does prevent electrolyte degradation due to the reductive nature of Mg. However, undesirable properties such as defects and layer breakdown lead to Mg growth that causes soft-shorting. The soft-shorting occurs with and without the protection layer, indicating the ALD layer does not prevent it and hinders Al2O3 from being an ideal candidate for a protection layer. Crucial effects of this layer on Mg electrochemistry at the interface were observed, including growth of Mg deposits leading to soft-shorting of the cell whose morphology showed a dependence on the Al2O3 layer. These results may provide guidelines for the future design and development of protective ASEI layers for Mg anodes.